SoxB2 in sea urchin development: implications in neurogenesis, ciliogenesis and skeletal patterning - Evgeniya Anishchenko; Maria Ina Arnone; Salvatore D’Aniello (EvoDevo, 2018)
Abstract Background Current studies in evolutionary developmental biology are focused on the reconstruction of gene regulatory networks in target animal species. From decades, the scientific interest on genetic mechanisms orchestrating embryos development has been increasing in consequence to the fact that common features shared by evolutionarily distant phyla are being clarified. In 2011, a study across eumetazoan species showed for the first time the existence of a highly conserved non-coding element controlling the SoxB2 gene, which is involved in the early specification of the nervous system. This discovery raised several questions about SoxB2 function and regulation in deuterostomes from an evolutionary point of view. Results Due to the relevant phylogenetic position within deuterostomes, the sea urchin Strongylocentrotus purpuratus represents an advantageous animal model in the field of evolutionary developmental biology. Herein, we show a comprehensive study of SoxB2 functions in sea urchins, in particular its expression pattern in a wide range of developmental stages, and its co-localization with other neurogenic markers, as SoxB1, SoxC and Elav. Moreover, this work provides a detailed description of the phenotype of sea urchin SoxB2 knocked-down embryos, confirming its key function in neurogenesis and revealing, for the first time, its additional roles in oral and aboral ectoderm cilia and skeletal rod morphology. Conclusions We concluded that SoxB2 in sea urchins has a neurogenic function; however, this gene could have multiple roles in sea urchin embryogenesis, expanding its expression in non-neurogenic cells. We showed that SoxB2 is functionally conserved among deuterostomes and suggested that in S. purpuratus this gene acquired additional functions, being involved in ciliogenesis and skeletal patterning.